Pengaruh Literasi Keuangan Terhadap Minat Pemilihan Produk Perbankan Syariah Di Kalangan Mahasiswa - Minando, Haris; Handayani, Agustia; Ekawati, Farida (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
The choice of Islamic banking products among students is becoming an increasingly interesting issue in the development of the Islamic banking sector. The younger generation, including students, has a crucial role in shaping the future direction of Islamic banking. An important factor that is believed to influence the decision to choose Islamic banking products by students is the level of financial literacy. This study aims to investigate the effect of financial literacy on the interest in choosing Islamic banking products among university students. The survey method through questionnaires was used on 68 respondents of Islamic banking study program students. The results showed that the thitung value was 25.181 > ttabel 2.000 and it was found that the fhitung value exceeded the ftabel value, which was 634.100 > 3.986, with a significance value of 0.000, which is smaller than the significance value of 0.05. From these results, Islamic financial literacy has a significant influence on the interest in choosing Islamic banking products among students. The coefficient of determination reached 90.4%, indicating a strong influence. Support from religious aspects is also important in the selection of Islamic banking products, by Islamic principles that emphasize fairness and understanding in transactions. This study is consistent with previous findings by Nahla Zamharira et al. (2021), which also shows that Islamic financial literacy has a significant impact on students' decisions to utilize Islamic banking services. In conclusion, the higher the Islamic financial literacy, the more interest in choosing Islamic banking products in college students.